Applying Moral Education Concept According to K.H. Hashim Asy'ari to Changes in Student Behavior - Ali, Syamsuri; Septuri, Septuri; Sahal, M. Ichsan Nawawi (International Journal Labs, 2023)
Background: Today, education is more concerned with material and scientific issues than ethics, morals and morals. High decadence or moral decline indicates a moral crisis that is very concerning. Education should be able to touch various physical, spiritual, moral, ethical, psychological and physical aspects. Otherwise, education is like just a teaching, and nothing reaches students at all. Aim: This study aims to analyze the concept of akhlaq education according to K.H. Asy'ari in the book of Adab Al-Alim Wa Al-Muta’alim on students' behavior change. Method: The type of research that the author did was descriptive quantitative research. This research also involves a literature study approach to obtain deeper information about moral education in the book of Adab Al-Alim Wa Al-Muta'alim The source of data in research is the subject from which data can be obtained. Findings: All students in MAN 1 Bandar Lampung have actually applied good moral education to their teachers. However, on a number of indicators, there are still those who answer neutrally and are not even sure that they have implemented moral education.